In vitro MIC of Itraconazole Against Different Isolates of Candida albicans - Inssaf I. Al- shemmary (College of Pharmacy University of Baghdad, 2017)
In vitro antifungal susceptibility test of itraconazole was carried out against 38 isolates from nails, skin, oral cavity, vagina and wounds, This study was done in Ramadi Teaching Hospital in period from January to August 2010. According to the National Committee for Clinical Laboratory Standard (NCCLS ) M 27- A by using the broth dilution method. Inoculum size was 1-5X103 CFU/ ml, while final concentrations of itraconazole ranged from 0.025 â€" 6.4 Î¼g / ml by using RPMI â€" 1640 broth media and the fungus was incubated at 35 oC.  No resistant stain was recorded. MIC ranged from 0.05 â€" 6.4 Î¼g / ml and the Mean Â± SEM was 0.89 Â± 0.28. MIC for nail isolates was 0.05 â€" 6.4 Î¼g/ ml, for skin isolates it was 0.05 â€" 6.4 Î¼g / ml, for oral cavity isolates it was 0.05 â€" 0.4 Î¼g/ ml, for vagina isolates it was  0.1 â€" 6.4 Î¼g / ml and for wound isolates it was 0.1 â€" 1.6 Î¼g/ ml.  MIC50 was 0.2 Î¼g / ml and MIC90 was 1.6Î¼g / ml. Itraconazole acts as fungistatic more than fungicidal agent; in 25( 65.8% ) isolates it acts as fungistatic and as fungicidal in 13 (34.2 % ) isolates. Key words: Itraconazole, C. albicans.